2005
DOI: 10.1177/0269881105048900
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tolerance to recreational MDMA (3,4-methylenedioxymethamphetamine) or Ecstasy

Abstract: This review of chronic tolerance to MDMA (3,4-methylenedioxymetamphetamine) covers the empirical data on dosage escalation, reduced subjective efficacy and bingeing in recreational Ecstasy users. Novice users generally take a single Ecstasy tablet, regular users typically take 2-3 tablets, whereas the most experienced users may take 10-25 tablets in a single session. Reduced subjective efficacy following repeated usage is typically described, with many users subjectively reporting the development of tolerance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(215 citation statements)
references
References 96 publications
11
202
1
1
Order By: Relevance
“…Third, as described in this review, self-administration of MDMA and its analogs is a reasonably robust phenomenon, particularly in the rhesus monkey (but see De La Garza's review in this issue for a discussion of the challenges in maintaining rodent self-administration of MDMA). Finally, the progressive loss of MDMA selfadministration behavior previously noted in rhesus monkeys replicates the similar phenomenon of spontaneous abstinence in human users (von Sydow et al 2002;Parrot 2005), and may be a novel and sensitive behavioral model for the persistent neurochemical effects of the drug. In approximately 20 years of MDMA research, only a handful of studies have employed self-administration techniques to study the effects of this compound.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Third, as described in this review, self-administration of MDMA and its analogs is a reasonably robust phenomenon, particularly in the rhesus monkey (but see De La Garza's review in this issue for a discussion of the challenges in maintaining rodent self-administration of MDMA). Finally, the progressive loss of MDMA selfadministration behavior previously noted in rhesus monkeys replicates the similar phenomenon of spontaneous abstinence in human users (von Sydow et al 2002;Parrot 2005), and may be a novel and sensitive behavioral model for the persistent neurochemical effects of the drug. In approximately 20 years of MDMA research, only a handful of studies have employed self-administration techniques to study the effects of this compound.…”
Section: Discussionsupporting
confidence: 64%
“…It has been suggested that these data may indicate the development of chronic tolerance to the effects of MDMA (Parrot 2005); however, it may be more difficult to assert that tolerance has developed to the reinforcing effects of a drug than is commonly appreciated. In the case of complete tolerance to the reinforcing effects of a drug, it seems reasonable to assume that the drug would lose its capacity to engender self-administration (as no amount of drug could be taken that could serve the function of maintaining the behavior) and extinction would thus ensue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study utilized large MDMA challenge doses, and so a robust effect on locomotor stimulation might have offset diminished serotonin stores, although the latter were not quantitated at 4 days. Since the duration of treatment was so brief, this finding is not necessarily relevant to reports of gradual tolerance to the subjective effects of MDMA nor to reports of supersensitivity which occurs after longer treatment durations (Parrot 2005). Females but not males showed sensitized responding when tested 2 weeks after the last treatment.…”
Section: Discussionmentioning
confidence: 71%
“…There have been several studies in which MDMA was administered to humans in a controlled laboratory setting and in which plasma pharmacokinetics of MDMA were measured (Helmlin et al, 1996;de la Torre et al, 2000de la Torre et al, , 2004Pacifici et al, 2001Pacifici et al, , 2002. However, these studies necessarily involved a limited dose range that was well below that reported by some MDMA users (Parrott, 2005). Further, it is possible that factors associated with MDMA use in dance settings (eg increased temperature, crowding, activity, ingestion of other psychoactive substances) may influence the pharmacokinetics, pharmacodynamics, and/or neurotoxic potential of MDMA.…”
Section: Introductionmentioning
confidence: 99%